Pengaruh Kualitas Pelayanan, Kinerja Pegawai, dan Kompetensi Pegawai terhadap Kepuasan Masyarakat pada Kantor Balai Desa Krakahan - Sulisti Zulia Aprilianti; Nur Khojin; Ari Kristiana; Slamet Bambang Riono; Mohamad Badrun Zaman (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to examine the influence of service quality, employee performance, and employee competence on community satisfaction at the Krakahan Village Hall Office. The background of this study is based on the importance of public service quality in improving community satisfaction and the role of employee performance and competence in providing optimal service. This research uses a quantitative approach with an associative method. The sample of this study consists of 150 community members who use services at the Krakahan Village Hall Office. The sampling method used is simple random sampling. Data were collected through questionnaires measuring service quality, employee performance, employee competence, and community satisfaction. Data analysis was performed using multiple linear regression and SPSS software. The results showed that service quality has a significant positive effect on community satisfaction. Employee performance also has a significant positive impact, while employee competence shows a significant positive effect on community satisfaction. Simultaneously, all three variables significantly contribute to community satisfaction at the Krakahan Village Hall Office. This study emphasizes the importance of improving service quality, employee performance, and competence to enhance community satisfaction.